Cinderella Man : James J. Braddock, Max Baer, and the greatest upset in boxing history - Schaap, Jeremy (Boston : Houghton Mifflin, 2005)
Boxing's true Cinderella story: James J. Braddock, dubbed "Cinderella Man" by Damon Runyon, was a once promising light heavyweight for whom a string of losses and a broken right hand happened to coincide with the Great Crash of 1929. With one good hand, he was forced to labor on the docks of Hoboken. Only his manager still believed in him. The diminutive, loquacious Jew and the burly, quiet Irishman made one of boxing's oddest couples, but together they staged the greatest comeback in fighting history. Braddock went from the relief rolls to face heavyweight champion Max Baer, the Livermore Butcher Boy, renowned for having allegedly killed two men in the ring. A charismatic, natural talent, Baer was a towering, brash opponent. A ten-to-one underdog, Braddock's unlikely upset made him the most popular champion boxing had ever seen. Against the gritty backdrop of the Depression, this book brings this all-American story to life, evoking a time when the sport of boxing resonated with a country trying desperately to get back on its feet.
Corn and hash -- Battle of Nurge's Field -- Meat inspector -- Livermore butcher boy -- Spooked by the phantom -- Great white way -- Crash and the jinx -- Lord of the jungle -- Star of David -- On the waterfront -- Last one up's a Sissy -- Another upset -- King Max -- Shot at Lasky -- People's choice -- Homicide hall -- Stout heart -- Epilogue -- Appendix A: Heavyweight championship -- Appendix B: James J. Braddock's ring record -- Appendix C: Max Baer's ring record.
Includes bibliographical references and index.
Keywords: Braddock, James J. -- 1905-1974.; Baer, Max, -- 1909-1959.; Boxers (Sports) -- United States -- Biography; Sports rivalries -- United States